Perkembangan dan Implementasi Akuntansi Syariah di Indonesia: Tinjauan Literatur atas Tantangan, Peluang, dan Dampaknya - Salma Rosyidah (LPPM Universitas Bina Sarana Informatika, 2025)
The growing expansion of Indonesia’s Islamic finance industry has created an urgent need for a robust and standardized framework for Islamic accounting. Despite the increasing demand, the implementation of Islamic accounting still faces conceptual, regulatory, and operational challenges that hinder its optimal practice across financial and non-financial institutions. This study aims to examine the development and implementation of Islamic accounting in Indonesia by identifying its major challenges, emerging opportunities, and the overall impact on institutional performance and compliance with Islamic principles. This research employs a literature-based method by synthesizing findings from scholarly articles that discuss the conceptual foundations, regulatory frameworks, sectoral applications, and technological developments related to Islamic accounting. The findings reveal that the growth of Islamic accounting is strongly supported by regulatory advancements and institutional commitment, yet constrained by limited professional competence, inconsistent application of standards, and inadequate technological infrastructure. The results also indicate that the adoption of Islamic accounting enhances transparency, strengthens governance, and improves stakeholder trust, demonstrating its strategic role in reinforcing ethical and Sharia-compliant financial practices. The novelty of this study lies in its comprehensive integration of theoretical, regulatory, and practical perspectives, as well as its identification of emerging research directions, particularly in digital transformation and the modernization of Sharia-based reporting practices. This study contributes to a deeper understanding of the position of Islamic accounting within Indonesia’s evolving economic landscape.